2012
DOI: 10.1029/2011jb008966
|View full text |Cite
|
Sign up to set email alerts
|

The East Anatolian Fault Zone: Seismotectonic setting and spatiotemporal characteristics of seismicity based on precise earthquake locations

Abstract: [1] The East Anatolian Fault Zone (EAFZ) represents a plate boundary extending over $500 km between the Arabian and Anatolian plates. Relative plate motion occurs with slip rates ranging from 6 to 10 mm/yr and has resulted in destructive earthquakes in eastern Turkey as documented by historical records. In this study, we investigate the seismic activity along the EAFZ and fault kinematics based on recordings from a densified regional seismic network providing the best possible azimuthal coverage for the target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 56 publications
5
57
1
Order By: Relevance
“…Current deformation is mainly accommodated through strain localization along the North Anatolian Fault (NAF) and the East Anatolian Fault (EAF). The deformation along the EAF is purely left lateral with no compressional component except for localized thrust ridges associated with strike-slip tectonics (Bulut et al, 2012). Body wave tomography images on global and regional scale indicate that the Hellenic subduction penetrates down to the lower mantle with an average dip of about 40 • (Wortel and Spakman, 2000;Faccenna et al, 2006;Biryol et al, 2011;Salaün et al, 2012) while a recent waveform tomography study by Fichtner et al (2013a, b) did not report any deep slab.…”
Section: Introductionmentioning
confidence: 85%
“…Current deformation is mainly accommodated through strain localization along the North Anatolian Fault (NAF) and the East Anatolian Fault (EAF). The deformation along the EAF is purely left lateral with no compressional component except for localized thrust ridges associated with strike-slip tectonics (Bulut et al, 2012). Body wave tomography images on global and regional scale indicate that the Hellenic subduction penetrates down to the lower mantle with an average dip of about 40 • (Wortel and Spakman, 2000;Faccenna et al, 2006;Biryol et al, 2011;Salaün et al, 2012) while a recent waveform tomography study by Fichtner et al (2013a, b) did not report any deep slab.…”
Section: Introductionmentioning
confidence: 85%
“…Similarly, Burton et al [1984] stated, based on analysis of the seismicity between 1900 and 1978, that the seismic activity of the EAF seemed surprisingly low and that it might be an area where seismic creep is dominant. In addition, Bulut et al [2012] recently found low seismicity rates along the eastern half of the EAF (38 ı E-41 ı E) for the time period 2007-2011. Periods of low seismic activity in this area have also been identified in the past 500 years, e.g., during the 250 years from 1544 to 1789 [Ambraseys, 1989].…”
Section: Discussionmentioning
confidence: 99%
“…The estimates of the accumulated overall offset along the EAF vary between an upper range of 27-33 km that is recorded by geological features and the length of the Gölbaşı strike-slip basin Bulut et al, 2012) and a lower range of 15-22 km that is defined by drainage channel offsets on individual fault segments (Hempton, 1987;Bulut et al, 2012). Studies based on the geologic and geomorphic data along the EAF provide slip rates of between 6 and 11 mm/year (Arpat and Şaroğlu, 1975;Kiratzi, 1993;Westaway, 1994;Yürür and Chorowicz, 1998;Çetin et al, 2003;Aksoy et al, 2007;Herece, 2008;Emre, 2013, Yönlü et al, 2013), whereas GPS studies provide a constant slip rate of ~10 mm/year along the whole EAF (Reilinger et al, 2006;Mahmoud et al, 2013;Aktuğ et al, 2016).…”
Section: Seismotectonic Settingmentioning
confidence: 99%